ANALYSIS OF BITCOIN'S IMPACT ON USERS AND THEIR IMPACT ON THE VALUE OF THE RUPIAH AND THE ROLE OF THE GOVERNMENT IN THE PRESENCE OF BITCOIN - Cut Nova Rianda (Jurnal Ilmiah Teunuleh, 2021)
Bitcoin has a peer to peer system that is in contrast to financial system by eliminating third parties in transactions. Countries in the world have different positions on Bitcoin, there are countries that are accept, reject or not both, so that understanding is needed more in depth to the factors that determine the position of the country above Bitcoin. This study aims to look for the influence of the development of Bitcoin, the performance of fiat money and the governance systems of countries in the world in determining its position on the legality of Bitcoin. Theories and concepts used inside this research is the international financial system and the state management system; with a quantitative approach as well as multinomial logistic regression analysis supported with secondary data. The results of the analysis in this study revealed that of the nine factors affecting the country's top position Bitcoin; it's just that the significance is different. Influencing Factors significant in determining the country's position on Bitcoin are factors political and economic factors have no significant effect. So it can be said that state acceptance of Bitcoin tends to be caused political reasons compared to the economy, even though Bitcoin itself is located on economic aspects. If Bitcoin acceptance is legalized, then the countries in the world still must accompany the role of government because Bitcoin is judged not to have clear rules and potentially detrimental to others.